Human facial neural activities and gesture recognition for machine-interfacing applications - Preecha Yupapin; None Hamedi; None Salleh; None Tan; None Ismail; None Ali; None Dee-Uam; None Pavaganun (My University, 2011)
Abstract: The authors present a new method of recognizing different human facial gestures through their neural activities and muscle movements, which can be used in machine-interfacing applications. Human–machine interface (HMI) technology utilizes human neural activities as input controllers for the machine. Recently, much work has been done on the specific application of facial electromyography (EMG)-based HMI, which have used limited and fixed numbers of facial gestures. In this work, a multipurpose interface is suggested that can support 2–11 control commands that can be applied to various HMI systems. The significance of this work is finding the most accurate facial gestures for any application with a maximum of eleven control commands. Eleven facial gesture EMGs are recorded from ten volunteers. Detected EMGs are passed through a band-pass filter and root mean square features are extracted. Various combinations of gestures with a different number of gestures in each group are made from the existing facial gestures. Finally, all combinations are trained and classified by a Fuzzy c-means classifier. In conclusion, combinations with the highest recognition accuracy in each group are chosen. An average accuracy >90% of chosen combinations proved their ability to be used as command controllers. Keywords: neural system, neural activity, electromyography, machine learning, muscle activity
Keywords: Interfacing; Facial muscles; Interface (matter); EEG and Brain-Computer Interfaces